Analisis Sarana Prasarana & Pola Latihan untuk Meningkatkan Motivasi Siswa Meraih Kejuaraan Futsal dalam Event Pop Kota Cirebon - Ryu Pramuja, Marcellino; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the role of facilities and structured training patterns as motivators for students in achieving success in the sport of futsal at the POP Kota Cirebon event among students of SMPN 1 Kota Cirebon. The research uses a qualitative approach with a case study design. The research participants consisted of representatives of futsal athletes from SMPN 1 Kota Cirebon who participated in the POP Kota Cirebon, the supervising teachers, and the school principal, selected thru purposive sampling technique. Data collection techniques were carried out thru semi-structured interviews, observations, and documentation, then analyzed using data triangulation techniques and with the help of NVivo software. The research results show that the availability of adequate facilities and infrastructure, such as field conditions, training equipment, and supporting facilities, contributes to creating a comfortable and safe training environment. Furthermore, a systematically structured training regimen, including technical, tactical, physical, and mental exercises, can enhance students' discipline, self-confidence, and training enthusiasm. In conclusion, the achievement of the SMPN 1 Kota Cirebon futsal team in the POP Kota Cirebon competition is the result of the integration of adequate facilities, structured training programs, continuous evaluation, strong player selection, and high student motivation, which together build a tradition and ambition to achieve victory. Keywords: Student Motivation, Structured Training Patterns, Achievement, Facilities and Infrastructure